2007
DOI: 10.1021/pr070132s
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Trypsin on Superparamagnetic Nanoparticles for Rapid and Effective Proteolysis

Abstract: In this work, a novel and facile route was developed for the immobilization of enzyme on nanosized magnetic particles, and its application to fast protein digestion via a direct MALDI-TOF mass spectrometry analysis was demonstrated. At first, amine-functionalized magnetic particles with high magnetic responsivity and excellent dispersibility were prepared through a facile one-pot strategy. Then, magnetic nanoparticles were functionalized with numerous aldehyde(-CHO) groups by treating the as-synthesized, amine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
2
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 37 publications
3
77
2
3
Order By: Relevance
“…MALDI-TOF MS analysis also showed high sequence coverage (89%). The value of sequence coverage was higher than the other trypsin-immobilized reactors reported (Li et al, 2007a;Liu et al, 2009) and the same as that performed by in-solution digestion (37 ºC for 18 hours), suggesting that the immobilized TY showed rapid and efficient proteolysis. The multi-digestion of Cyt-C by the tandem microreactor that was connected by using TYmicroreactor and CT-microreactor was evaluated.…”
Section: Wwwintechopencommentioning
confidence: 62%
See 3 more Smart Citations
“…MALDI-TOF MS analysis also showed high sequence coverage (89%). The value of sequence coverage was higher than the other trypsin-immobilized reactors reported (Li et al, 2007a;Liu et al, 2009) and the same as that performed by in-solution digestion (37 ºC for 18 hours), suggesting that the immobilized TY showed rapid and efficient proteolysis. The multi-digestion of Cyt-C by the tandem microreactor that was connected by using TYmicroreactor and CT-microreactor was evaluated.…”
Section: Wwwintechopencommentioning
confidence: 62%
“…Similar to the digestion of lysozyme, the digestion of BSA by TY-microreactor at 50 °C efficiently occurred but not at 30 °C. The sequence coverage of 37% (201/583 amino acids) was higher compared with that of in-solution digestion (26%, 151/583 amino acids) and was better or comparable to those of a thermal (Liu et al, 2009;Sim et al, 2006) or chemical denatured BSA (Li et al, 2007a;Chatterjee et al, 2010) or the reduced BSA (Ma et al, 2008) by the reported trypsin-microreactors (24-46%). In addition, the number of identified disulfide bonds was 10 of 17, which is superior to 6 obtained by in-solution digestion.…”
Section: In Addition It I S P O S S I B L E T H a T O U R M S S Y S mentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, the IMERs can be reused hundreds of times. To date, many IMERs [4][5][6][7][8][9][10][11][12] have been designed and applied successfully. Monolith based IMERs [8][9][10][11][12] prepared in capillaries have been particularly popular because of the monolithic relatively high binding capacity for enzymes, low backpressure, biological inertia, and mechanical stability.…”
mentioning
confidence: 99%